2008
DOI: 10.35699/2675-5327.2007.23195
|View full text |Cite
|
Sign up to set email alerts
|

Borboletas (Lepidoptera) de um fragmento de mata urbano em Minas Gerais, Brasil

Abstract: The butterfly fauna of a small forest fragment in the campus of the Pontifícia Universidade Católica de Minas Gerais was surveyed between March and November 2001. The adult butterflies were captured using hand nets and frugivorous traps. In addition, caterpillars were raised in the laboratory for identification after emergence. Ninety-one species of six families were recorded. Among them, 46.1% belonged in Nymphalidae; 28.5% in Hesperiidae; 15.4% in Pieridae; 4.4% in Riodinidae; 4.4% in Papilionidae; and 1.1% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 6 publications
(11 reference statements)
2
3
0
2
Order By: Relevance
“…In similar environments of Semideciduous Seasonal Forest, in different cities in the south of Minas Gerais, Vieira et al (2020) found this community representing 58.54% of the identified Lepidoptera. This pattern was also pointed out by different studies and in different phytophysiognomies, such as Oliveira, Milani and Souza (2018) who recorded 57% of nymphalids, Andrade et al (2017) with 73.56%, Silva, Landa andVitalino (2007) with 46.1% andAraújo et al (2015) with 73.9%. This fact can be explained by the great diversity of food niches presented by these organisms (BROWN JUNIOR et al, 1999).…”
Section: Resultssupporting
confidence: 54%
“…In similar environments of Semideciduous Seasonal Forest, in different cities in the south of Minas Gerais, Vieira et al (2020) found this community representing 58.54% of the identified Lepidoptera. This pattern was also pointed out by different studies and in different phytophysiognomies, such as Oliveira, Milani and Souza (2018) who recorded 57% of nymphalids, Andrade et al (2017) with 73.56%, Silva, Landa andVitalino (2007) with 46.1% andAraújo et al (2015) with 73.9%. This fact can be explained by the great diversity of food niches presented by these organisms (BROWN JUNIOR et al, 1999).…”
Section: Resultssupporting
confidence: 54%
“…The richness obtained in the present study is nearly (SILVA et al, 2007;SACKIS & MORAIS, 2008;PEREIRA et al, 2015) or it is bigger (VASCONCELOS et al, 2009;SOARES et al, 2012;BOGIANI et al, 2012) than many of the major urban butterfly inventories in Brazil, conducted with sampling effort and relatively distinct methodologies in the Pampa, Cerrado and Atlantic Forest biomes, and it is much lower in five of the eleven works used for comparison (PINHEIRO et al, 2008;BONFANTTI et al, 2009BONFANTTI et al, , 2011LEMES et al, 2015;MELO et al, 2019); it is observed that less than half of the CSTR species have distribution records for these urban areas, except one, described in Table III. In compensation, most of the recorded species are shared with the available inventories for the Caatinga biome, Semiarid region, carried out in different phytophysiognomies of the ecoregions of Meridional Sertaneja Depression, Borborema Plateau, Chapada Diamantina Complex, Ibiapaba-Araripe Complex and Campo Maior Complex; although they have a considerably larger number of species, because they are more conserved environments and, also, they are outside the urban matrix (Table IV).…”
Section: Resultssupporting
confidence: 47%
“…Simple comparisons of richness and composition were also made with the intention to achieve some similarity with other available inventories for urban green areas in the Pampa, Cerrado and Atlantic Forest biomes (SILVA et al, 2007;SACKIS & MORAIS, 2008;PINHEIRO et al, 2008;BONFANTTI et al, 2009;VASCONCELOS et al, 2009;BONFANTTI et al, 2011;SOARES et al, 2012;BOGIANI et al, 2012;PEREIRA et al, 2015;LEMES et al, 2015;MELO et al, 2019), and with the other inventories developed in the northeastern Semiarid region (NOBRE et al, 2008;PALUCH et al, 2011;ZACCA & BRAVO, 2012;LIMA & ZACCA, 2014;KERPEL et al, 2014;RAFAEL et al, 2017). New records for the Northeast region were obtained from the inventories available in scientific literature (CARDOSO, 1949;KESSELRING & EBERT, 1982;NOBRE et al, 2008;ZACCA et al, 2011;PALUCH et al, 2011;ZACCA & BRAVO, 2012;LIMA & ZACCA, 2014;KERPEL et al, 2014;PALUCH et al, 2016;RAFAEL et al, 2017;MARTINS et al, 2017;PEREIRA et al, 2018;MELO et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As várias mudanças e modificações na paisagem de uma área, principalmente pelo processo de urbanização, tem levado à destruição ou fragmentação de habitats, o que torna as áreas remanescentes importantes refúgios para a fauna e a flora (FAHRIG, 2003;SILVA et al, 2007). Algumas características marcantes que diferenciam os habitats fragmentados dos naturais são, além da diminuição da sua área, um aumento considerável da área de borda (LANGANKE, 2011).…”
Section: Introductionunclassified